Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Systemic Sclerosis - Sumartini Dewi (Indonesian Rheumatology Associantion, 2025)
Background: Systemic Sclerosis (SSc) or Scleroderma is a systemic autoimmune rheumatic disease characterized by dysregulation of the immune system, fibrosis of the skin and visceral organs and vasculopathy. The global prevalence of SSc reaches 17.6 per 100,000 population and the incidence reaches 1.4 per 100,000 people per year. The prevalence and incidence of SSc in Asia reaches 6.8 per 100,000 and 0.9 per 100,000, which is lower than other continents. Women have a prevalence and incidence of SSc five times higher than men. The prevalence and incidence of SSc depends greatly on the results of the study. There has not been much research on the epidemiological studies of SSc in Indonesia. Methods: Twelve selected rheumatologists from the Indonesian Rheumatologist Association (IRA) made recommendations based on key questions formed by a steering committee from IRA. These recommendation materials were taken from several online databases such as PubMed, Science Direct, and Google Scholar. Level of evidence and grades of recommendation were then assigned, and every member of the panelist team will assign a score for level of agreement. Results: A total of 50 recommendations that discussed the diagnosis, pharmacological and non- pharmacological therapy, and prognosis for SSc were made. Conclusion: These recommendations can be used to help clinicians correctly diagnose and choose the most suitable therapy for SSc patients. All recommendation statements were created with the consideration of Indonesia’s clinical setting, facility, and drug availability.